Auditory network connectivity in tinnitus patients: a resting-state fMRI study - Davies, J.; Gander, P.E.; Andrews, M.; Hall, D.A. (Informa Healthcare, 2014)
Objective: Resting-state functional magnetic resonance imaging (fMRI) uncovers correlated activity between spatially distinct functionally related brain regions and offers clues about the integrity of functional brain circuits in people with chronic subjective tinnitus. We chose to investigate auditory network connectivity, adopting and extending previously used analyses methods to provide an independent evaluation of replicability. Design: Independent components analysis (ICA) was used to identify coherent patterns arising from spontaneous brain signals within the resting-state data. The auditory network component was extracted and evaluated. Bivariate and partial correlation analyses were performed on pre-defined regions of bilateral auditory cortex to assess functional connectivity. Study sample: Our design carefully matched participant groups for possible confounds, such as hearing status. Twelve patients (seven male, five female; mean age 66 years) all with chronic constant tinnitus and eleven controls (eight male, three female; mean age 68 years) took part. Results: No significant differences were found in auditory network connectivity between groups after correcting for multiple statistical comparisons in the analysis. This contradicts previous findings reporting reduced auditory network connectivity; albeit at a less stringent statistical threshold. Conclusions: Auditory network connectivity does not appear to be reliably altered by the experience of chronic subjective tinnitus.